AN ASSESSMENT OF THE MACROECONOMIC DETERMINANTS OF DEMAND FOR LIFE INSURANCE PRODUCTS: EMPIRICAL FROM NIGERIA - Adedeji Daniel Gbadebo (J-MACC, 2024)
Life insurance also serves as a social mechanism for covering expenses related to death and supporting dependents. This study aimed to explore how national income, inflation rates, real interest rates, life expectancy, and dependency ratios influence the demand for life insurance products in Nigeria. A fixed effect model was fitted on sourced data over the period from 1980 to 2023. The paper finds that a positive but statistically insignificant relationship with life insurance demand was observed, indicating a weak impact. Both variables did not significantly affect life insurance demand, supporting the hypothesis that these economic factors have minimal influence. A significant positive relationship with life insurance demand was found. This suggests that as life expectancy increases, so does the demand for life insurance, highlighting the importance of long-term financial planning. A significant negative relationship with life insurance demand was identified, indicating that a higher ratio of dependents to income earners results in lower demand for insurance products. These findings provide a nuanced understanding of the determinants of life insurance demand in Nigeria, emphasizing the varying impacts of socio-economic and demographic factors.